The warden's daughter - Spinelli, Jerry (Yearling, 2018)
Cammie O'Reilly is an unusual kid with an even more unusual home life. She hangs out with a flamboyant black shoplifter named Boo Boo, her housekeeper is a sullen arsonist named Eloda Pupko, and she lives above the entrance of a prison where her dad is the warden. Trying to cope with the death of her mother, who died saving Cammie's life, causes Cammie to become a depressed, angry tween, driven mad by her life in prison. The more Cammie tries to figure out who she is, the more she spirals into depression, until someone close to her makes the ultimate sacrifice to free Cammie from her past.